SOSIALISASI PENCEGAHAN KECACINGAN MELALUI PERILAKU HIDUP SEHAT PADA SISWA SD N 4 KALISARI - Gigih Kenanga Sari; Dhiva Mariska; Errika Febriyana; Fina Ardiana Maharani; Siti Nur Aisah (LPPM AN Nuur, 2025)
Background: Helminthiasis remains a significant health issue in Indonesia, especially among children in rural areas. Poor environmental factors, such as inadequate sanitation, and low public awareness of the importance of personal hygiene contribute to the high prevalence of helminth infections. Purpose: To enhance the understanding of Grade VI students at SDN 4 Kalisari regarding the dangers of helminthiasis and its prevention through healthy living practices. Method: Direct socialization through material presentation and proper handwashing practice. This activity was attended by 23 students and took place on November 30, 2024. Results: Most students understood the causes and preventive measures for helminthiasis, but some students were not yet accustomed to regularly practicing healthy habits, such as washing hands with soap. Collaboration between parents and teachers is needed to ensure the implementation of these healthy habits in daily life. Conclusion: This socialization is expected to contribute to the prevention of helminthiasis and raise awareness of the importance of personal hygiene among children.